Mandibular reconstruction with the scapula tip free flap. Issue 7 (14th March 2019) - Blumberg, Jeffrey M.; Walker, Paul; Johnson, Stephanie; Johnson, Bradley; Yu, Eugene; Lacasse, Marie‐Constance; Lam, David K.; Rittenberg, Brian; Yao, Christopher M.K.L.; Chepeha, Douglas; de Almeida, John R.; Goldstein, David P.; et al.
Abstract: Introduction: The scapula tip free flap has been described for reconstruction of short mandible defects with extensive soft tissue needs. The versatility of this flap has not been extensively described. Methods: Retrospective case series of patients who underwent mandibulectomy and reconstruction with the scapula tip free flap from 2005 to 2016. Outcomes include bony union, complications, dental rehabilitation, and donor site morbidity. Results: A total of 120 patients were identified. Average harvested bone was 7.7 cm, with 54% undergoing one osteotomy, and 76.7% harvested as a chimeric flap. Radiographically, average inset bone was 6.6 cm. Complete or partial bony union was observed at 74.4% of proximal and 82.6% of distal osteotomies. A 95% of reconstructions met criteria for dental implants. Mean disabilities of the arm, shoulder and hand score was 21.2. Conclusions: The scapular tip is an excellent option for reconstruction of segmental mandible defects with the option of osteotomy, excellent bony union rates, low donor site morbidity, and potential for dental rehabilitation.